Understanding Behavior Pattern of College Students Towards Social Networking Sites in India - Jha, Suchita; Chitnis, Asmita; Chitnis, Ravikumar (Indian Journal of Computer Science, 2019)
In India as well as globally, the usage of Social Networking Sites (SNS) among college students has increased significantly. Social networking has become an integral part of their lifestyle. The present study tries to explore the behavioral pattern of students towards social networking sites in India with respect to the time spent on various social networking platforms, number of friends (real or virtual) on social networking sites, kind of activities they are involved in on social networking sites and finding out the reason for hooking onto these virtual platforms. The study was conducted among undergraduate and post graduate students studying in Pune. From the sample data collected it was noticed that majority of users were having prominent presence on Facebook as compared to other social networking sites and therefore, the present study focuses on Facebook. Data collection was done with structured questionnaire and focus group interview. Analysis of the data suggests the fact that there is significant difference in behavior pattern between undergraduate and post graduate students. The reason for accessing social networking sites is not just chatting with friends but it also done for professional benefit and networking.